The Family as a Protective Factor: Economic considerations of Bangladeshi labour trafficking survivors - Caparas, Mary; Gapur, Nadia (Anti-Trafficking Review, 2025)
Economic dependence often exists within trafficked immigrant families, both before the human trafficking situation and after family reunification in the United States. While economic dependence can deepen individuals’ vulnerabilities to human trafficking, this article explores how the family unit can serve as a protective factor, especially for those who have recently experienced family reunification. Writing from the perspective of social service providers, we utilise a composite case study of several clients to exemplify how families can support and protect each other within their new environment in New York City and after reunifying with extended family members. This case study demonstrates that social service providers must adopt a family and community-centric approach to survivor support to ensure they strengthen the ability of the family unit to serve as a protective factor against further exploitation for trafficking victims in the US.